Resting state connectivity and cognitive performance in adults with cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy. Issue 5 (May 2016) - Cullen, Breda; Moreton, Fiona C; Stringer, Michael S; Krishnadas, Rajeev; Kalladka, Dheeraj; López-González, Maria R; Santosh, Celestine; Schwarzbauer, Christian; Muir, Keith W
Cognitive impairment is an inevitable feature of cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), affecting executive function, attention and processing speed from an early stage. Impairment is associated with structural markers such as lacunes, but associations with functional connectivity have not yet been reported. Twenty-two adults with genetically-confirmed CADASIL (11 male; aged 49.8 ± 11.2 years) underwent functional magnetic resonance imaging at rest. Intrinsic attentional/executive networks were identified using group independent components analysis. A linear regression model tested voxel-wise associations between cognitive measures and component spatial maps, and Pearson correlations were performed with mean intra-component connectivity z-scores. Two frontoparietal components were associated with cognitive performance. Voxel-wise analyses showed an association between one component cluster and processing speed (left middle temporal gyrus; peak −48, −18, −14; Z E = 5.65, p FWE corr = 0.001). Mean connectivity in both components correlated with processing speed ( r  = 0.45, p  = 0.043; r  = 0.56, p  = 0.008). Mean connectivity in one component correlated with faster Trailmaking B minus A time ( r  = −0.77, p  < 0.001) and better executive performance ( r  = 0.56, p  = 0.011). This preliminary study provides evidence for associations between cognitive performance and attentional network connectivity in CADASIL. Functional connectivity may be a useful biomarker of cognitive performance in this population.